2011
DOI: 10.1345/aph.1p274
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Therapy Using Enzymatic Anti-Factor IIa Monitoring

Abstract: TO THE EDITOR: Current treatment of heparin-induced thrombocytopenia (HIT) is replacement of heparin with a direct thrombin-inhibitor (DTI) such as argatroban. 1 The argatroban package insert recommends that initial dosage be based on patient weight. However, this may be suboptimal, since argatroban is distributed predominantly in blood and extracellular fluid and not in lean tissue and/or adipose. 2 Additionally, monitoring argatroban therapy is challenging because the gold standard assays are not routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…21 Our group and others have shown that TT is more reliable and robust for the monitoring of argatroban. 6,22 Figure 6A confirms a linear relationship between PAC and corresponding TT intervals. In contrast, the relationship between increasing PAC and correspondent simultaneous aPTT intervals is not linear, reaching a plateau for aPTT values above 70 s (Figure 6B), underscoring that this coagulation assay is less accurate for monitoring argatroban anticoagulation.…”
Section: Argatroban Laboratory Monitoring With Aptt and Thrombin Timesupporting
confidence: 56%
“…21 Our group and others have shown that TT is more reliable and robust for the monitoring of argatroban. 6,22 Figure 6A confirms a linear relationship between PAC and corresponding TT intervals. In contrast, the relationship between increasing PAC and correspondent simultaneous aPTT intervals is not linear, reaching a plateau for aPTT values above 70 s (Figure 6B), underscoring that this coagulation assay is less accurate for monitoring argatroban anticoagulation.…”
Section: Argatroban Laboratory Monitoring With Aptt and Thrombin Timesupporting
confidence: 56%
“…In the absence of organ failure, the dose recommended in the manufacturer's prescribing information is 2 μg/kg/min. However, several publications indicate that this dose is too high and that an initial dose of 1 μg/kg/min is adequate for patients without organ function impairment [22,29,30].…”
Section: How To Use the Drug In Patients With Hitmentioning
confidence: 99%
“…Antifactor IIa and/or aPTT monitoring is scheduled before and 2 hours after the start of the argatroban infusion (steadystate levels of drug and anticoagulant effect are expected after five half-lives), 2 hours after each dose adjustment and then daily. The proposed target argatroban concentration is 0.4-1.5 μg/ml [22,25]. The aPTT is aimed at 1.5−3.0 times the patient's baseline (provided baseline aPTT was within the reference range) without exceeding 100 sec with most reagents; the precise target range depends very much on the local reagent/coagulometer combination and has to be established in-house.…”
Section: How To Use Argatroban In Hit Subpopulationsmentioning
confidence: 99%
“…Specific chromogenic anti‐IIa assays are available for the measurement of drugs that inhibit thrombin, including DTIs (Shepherd et al , ; Harenberg et al , ). These assays should be calibrated with product‐specific calibrators which are available commercially for dabigatran and argatroban.…”
Section: Direct Thrombin Inhibitors (Dtis)mentioning
confidence: 99%